Evidence indicating that the cholera toxin structural genes of Vibrio cholerae RJ1 and 3083-2 are between met and trp. - Saunders, D W (1983)
An enterotoxin A subunit-specific radioactive probe was used to correlate expression of vct-1 or vct-2 with the presence of specific restriction fragments in the DNAs of several wild-type and recombinant Vibrio cholerae strains. The data are consistent with the conclusion that vct is a cholera toxin structural gene.